1995
DOI: 10.1095/biolreprod53.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Localization of the Testicular and Sperm-Specific Lactate Dehydrogenase Isozyme C4 in Mice1

Abstract: The proposed dual intracellular distribution of the sperm-specific lactate dehydrogenase (EC 1.1.1.27) isozyme C4 (LDH C4) has been based on indirect evidence. In order to obtain direct evidence on the localization of this LDH isozyme in mice, postembedding immunocytochemistry at ultrastructural level was performed on testes, epididymal spermatozoa, and isolated testicular mitochondria. The immunogold technique was applied to thin sections incubated first in partially purified specific anti-LDH C4 rabbit IgG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 34 publications
0
47
1
Order By: Relevance
“…Several ATP production-related proteins have been identified in the mitochondria of spermatozoa. For example, both spermspecific isoforms of lactate dehydrogenase catalyze the interconversion of pyruvate and lactate with concomitant interconversion of NADH and NAD + ; hexokinase catalyzes the conversion of glucose to glucose-6-phosphate in the initial step of glycolysis and is expressed at the mid-piece of mouse sperm [45,46]. HIBADH is an NAD + -dependent mitochondrial enzyme that catalyzes oxidation of 3-hydroxyisobutyrate, an intermediate of valine catabolism, to methylmalonate semialdehyde [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Several ATP production-related proteins have been identified in the mitochondria of spermatozoa. For example, both spermspecific isoforms of lactate dehydrogenase catalyze the interconversion of pyruvate and lactate with concomitant interconversion of NADH and NAD + ; hexokinase catalyzes the conversion of glucose to glucose-6-phosphate in the initial step of glycolysis and is expressed at the mid-piece of mouse sperm [45,46]. HIBADH is an NAD + -dependent mitochondrial enzyme that catalyzes oxidation of 3-hydroxyisobutyrate, an intermediate of valine catabolism, to methylmalonate semialdehyde [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…However, sperm mitochondria possess several unique proteins or protein isoforms that are not found in somatic mitochondria. In mice, these include sperm-specific isoforms of lactate dehydrogenase and hexokinase (Burgos et al 1995;Bunch et al 1998;Mori et al 1998;Travis et al 1998). Thus, defects in these spermspecific proteins may result only in problems with sperm mitochondrial function, rather than with mitochondrial dysfunction in all cells.…”
Section: Motors Need Fuel: the Mitochondrial Sheathmentioning
confidence: 99%
“…[8][9][10][11][12] In this study, we purified and characterized LDH-A4 from skeletal muscle of yak and cattle, and found that yak LDH-A4 Km for pyruvate was much higher than that of cattle. Yak LDH-A cDNA was cloned and analyzed in order to elucidate the amino acid substitutions between yak and cattle.LDH-A4 was purified from skeletal muscles of yak and Chinese yellow cattle by modification of the methods reported by Dissing et al (1998) and Burgos et al (1995). 13,14) Skeletal muscle tissues were homogenized in cold phosphate buffered saline (PBS), incubated for 4 h at 4 C, and centrifuged at 10,000 g for 20 min at 4 C. The supernatant was used as the crude extract, and ammonium sulfate was added to 80% saturation.…”
mentioning
confidence: 99%
“…LDH-A4 was purified from skeletal muscles of yak and Chinese yellow cattle by modification of the methods reported by Dissing et al (1998) and Burgos et al (1995). 13,14) Skeletal muscle tissues were homogenized in cold phosphate buffered saline (PBS), incubated for 4 h at 4 C, and centrifuged at 10,000 g for 20 min at 4 C. The supernatant was used as the crude extract, and ammonium sulfate was added to 80% saturation.…”
mentioning
confidence: 99%
See 1 more Smart Citation